Infection or allergy? The multifaceted nature of vulvar dermatoses - Alok Vij, MD; Apra Sood, MD; Melissa Piliang, MD; Natasha Atanaskova Mesinkovska, MD, PhD (Wolters Kluwer, 2015)
Chronic dermatitis or pruritus affecting the female genital and perianal skin can be challenging to properly diagnose and manage. The differential diagnosis generally includes allergic, inflammatory, infectious, and neoplastic conditions. We report the case of a 52-year-old woman with a 6-month history of a progressive, debilitating vulvar and perianal rash that highlights the multifaceted nature of female genital dermatoses.